THE FORM OF THE RELATIONSHIP BETWEEN CULTURAL, ARTISTIC, AND POETIC CONCEPTS - Ortiqov Eldor Mardonovich (Western European Studies, 2026)
This article explores the cognitive, cultural, and artistic aspects of poetic speech, concepts, and notions. Poetic speech is shaped by individual perception and contextual ethnolinguistic continuity. Concepts in poetic speech play a crucial role in transforming subjective experience into universal meanings, creating a semantic-associative system, and forming a speech-poetic continuum. A concept is interpreted as an ideal object reflecting cultural ideas in human consciousness, enabling reality perception through linguistic thinking. The article also discusses contemporary conceptualization theories, the stratification and evolution of notions, and their realization in poetic speech.
Keywords: poetic speech; cognitive phenomenon; concept